Avaliação dos métodos da tensão estrutural e curva mestre para determinação da vida em fadiga de juntas soldadas - Silveira, Júlio Azambuja da (2015)
The understanding of fatigue process has been demonstrated to be a challenge in the field of mechanical design, being significantly influenced by several factors, including, manufacturing process. Studies have pointed out that fatigue strength of a welded structure is governed by fatigue strength of the welded joint. In general, this assessment is carried out considering the joint as falling into a standardized class, according to geometry and loading conditions. Fatigue assessment of welded joints differ in the stress parameter adopted and can be classified as global (using nominal stresses, i.e., ignoring local effects of the joints) and local (using structural stresses that consider local effects of the joints). Despite providing more accurate results, the local method is more complex, and numerical tools like the Finite Element Method (FEM) become essential to its application. Using FEM, Dong (2001) proposed a methodology that permits the use of less complex numerical models without loss in accuracy. Furthermore, modifying the stress parameter of the S-N diagram in order to obtain an equivalent structural stress, it becomes possible to summarize the fatigue behavior of several class of joints into a single space of probabilities, the so-called Master Curve (MC). This work study different numerical models using shell finite elements to estimate the fatigue life of two kinds of welded joints, with experimental results available in the literature,in order to evaluate the applicability and accuracy of the master curve. The results are compared with the ones obtained using other method called Structural Hot Spot Stress, showing that this method yields conservative results for the fatigue life when compared to the Dong s method. It is worth noting the applied load level influences in accuracy of both methods. Among the different modeling techniques used, only one provided results that are not in agreement with the others when using the Dong s method. When analyzing fully symmetrical joints, the numerical modeling technique should not influence significantly the mechanical behavior of the joint predicted by the finite element model.